Antibacterial Activity Combination of Cefadoxil With 10 Plant Herbal Extract to Escherichia Coli Resistant and MRSA ( Methicillin-resistant Staphylococcus aureus ) - Liberitera, Sternatami; Ratna Yuliani, M. Biotech.St (2016)
Resistance is a serious problem in the therapy of infection. Escherichia coli and MRSA (methicillin-resistant S. aureus), the largest bacteria cause infections, are resistant to antibiotics, one of them is cefadroxil. Cefadroxil is combined with some extracts to improve the antibacterial activity against resitant E. coli and MRSA and as solution of the resistance problem. This study was done to determine the activity of the combination of cefadroxil with 10 medicinal plant extracts and the main compounds contained in the most potent extracts. Extraction was carried out using maceration method with 96% ethanol as solvent. Antibacterial activity was tested by placing extract disc (1 mg) on medium Mueller-Hinton Agar which had been inoculated with bacteria. DMSO/ ethanol was used as solvent control and cefadroxil was use as the antibiotic control. Combination of cefadroxil with extract was tested by placing the cefadroxil disk (30 µg), extract alone (1 mg), and combination of cefadroxil and extract on media which had been inoculated with bacteria. The most potentially extract was tested with thin layer chromatography (TLC) using mobile phase of toluene : ethyl acetate (97:3) and the stationary phase of silica gel GF254. The results showed that clove bud extract has the highest activity to inhibit the growth of resistant E. coli and MRSA. The combination of cefadroxil with some extracts showed that antibacterial activity of cefadroxil increased against MRSA and resistant E. coli. TLC test showed that clove extract contain eugenol.